Towards improving households' investment choices in Tanzania: Does financial literacy really matter? - Josephat Lotto (International Journal of Financial Studies, 2020)
This paper primarily aims to assess the impact of financial literacy on households' investment choices. The paper employs secondary data from the FinScope survey (2017) conducted by Financial Sector Deepening Trust (FSDT). In particular, the study aims at establishing whether the choices of investment platforms are influenced by the financial literacy level of the heads of households. To do so, the study employed both bivariate and multivariate analytical techniques. The study finds that financial literacy is positively and significantly associated with household investment choices. More specifically, as households become more financially literate, they divert from investing in informal groups towards more formal investment platforms such as investment accounts, agricultural ventures as well as personal business. Such observations may be partly attributable to the facts that individuals whose financial literacy is sound enough are more likely to be equipped with skills and knowledge of risks associated with investment opportunities and some other several financial products. The study also reveals that financial literacy is significantly associated with households' socio-demographic factors, and that the adult population exhibits a large financial literacy gap and, therefore, adults should not be considered as a homogenous group-instead, gender, age, education and income levels of the households, which are showcased in this study, should also be taken into consideration. The study opines that, because most of households, as revealed in the survey from which the employed dataset is based, are hailing from rural settings where agriculture is the main economic activity, we establish that agricultural ventures require a complete revamp for Tanzania to become a middle-income economy through its industrialization agenda. The study also proposes the financial literacy programmes to be rolled on to students from early stage of their education such as secondary schools.
Keywords: 330; education; age; financial literacy; gender; investment choices